The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.3354/cr015185
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between road slipperiness, traffic accident risk and winter road maintenance activity

Abstract: A method for deriving quantitative relationships between road slipperiness, traffic accident risk and winter road maintenance (WRM) activity is described. The method is also applied to data from an area in southern Sweden. If a specific type of road slipperiness represents a large accident risk despite high WRM activity it is important to increase public awareness during such periods. If the type of slipperiness represents a large accident risk but is accompanied by low WRM activity, it is also important to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 4 publications
6
65
0
2
Order By: Relevance
“…et al (1995) pointed out that weather conditions can play an important role in the accident-generation process, and Schandersson (1998) showed an increase in accident risk during snowfall. Norrman et al (2000) showed that accident risks varied considerably between the same slipperiness types used in this study. Since different types have a different impact on the road climate, they should be weighted accordingly.…”
Section: Planning Winter Maintenance and New Road Sectionsmentioning
confidence: 96%
“…et al (1995) pointed out that weather conditions can play an important role in the accident-generation process, and Schandersson (1998) showed an increase in accident risk during snowfall. Norrman et al (2000) showed that accident risks varied considerably between the same slipperiness types used in this study. Since different types have a different impact on the road climate, they should be weighted accordingly.…”
Section: Planning Winter Maintenance and New Road Sectionsmentioning
confidence: 96%
“…For instance, a study conducted by Forgas et al (2009) showed that people more easily remember "bad" weather. On the other hand, studies on driver behavior and cognition point to great problems related to drivers' lack of awareness of risks and perception of bad weather in the present, leading to increased accident frequency during the early winter season (e.g., Norman et al, 2000). Individuals' belief adjustment and revision of hypotheses based upon new evidence (Einhorn and Hogarth, 1985) is manifested as a "surprise effect" related to the number of days with "fair weather" conditions they experienced prior to severe events (Eisenberg, 2004).…”
Section: User Bias and Perception Of Weathermentioning
confidence: 99%
“…The Washington State Department of Transportation estimated that between 1992 and 2004 Snoqualmie Pass on Interstate Highway 90 (I-90) was closed 120 hr per year on average, causing an annual loss of at least 17.5 million dollars. Ice and snow also increase the risk of accidents (Norrman, Eriksson, and Lindqvist 2000;Eriksson and Norrman 2001). The crash rate on the I-90 Mountains to Sound Greenway, Washington State's primary east-west bound highway, in the presence of snow is about five times the rate in clear conditions (Federal Highway Administration 2006).…”
Section: Introductionmentioning
confidence: 99%